(untitled) (Al-Qalaa Journal, 2024)
This paper focuses on translating English tense and aspect into Arabic. The objective of this study is to investigate the ability of translation students to translate tense and aspect from English into Arabic to identify the difficulties they face in this regard. It is a case study that follows an observation method by asking students of the translation branch to translate twelve sentences, each representing an aspect, into Arabic. The population of the study includes the students of the translation branch at the Faculty of Arts and Sciences in Messalata. Students in their third and fourth years are selected as the sample for the study, and the entire sample consists of female students. Translations are evaluated according to Najeeb’s model of translating English tense and aspect into Arabic. The most important result indicates that students of the translation branch (third and fourth year) encounter difficulties in translating the continuous and perfect progressive aspects of English into Arabic.